Eidinemacheilus, a new generic name for Noemacheilus smithi Greenwood (Teleostei; Nemacheilidae) - Segherloo, Iraj Hashemzadeh; Ghaedrahmati, Nabiallah; Freyhof, Jörg (Zootaxa, 2016)
Eidinemacheilus, new genus, is described for the troglomorphic Noemacheilus smithi Greenwood. The sole species of the genus is endemic to an aquifer in the Karun River drainage in the Iranian Zagros Mountains. Eidinemacheilus smithi was identified as a species in Paracobitis as both genera share an elevated dorsal adipose crest, a character state being widespread in nemacheilid loaches. Eidinemacheilus is distinguished from all other genera of Nemacheilidae in the Middle East by having 7+7 branched caudal-fin rays, a strongly reduced head canal system, no pigmentation and no eyes. Eidinemacheilus smithi is also distinguished from other genera in the Middle East by a combination of the following character states: pelvic-fin origin behind of a vertical of the dorsal-fin origin, anus slightly in front of the anal-fin origin and no sexual dimorphism in the length of the paired fins. Eidinemacheilus, as a valid genus, is supported by the analysis of mitochondrial DNA data that shows no close affinity to Paracobitis or other nemacheilid genera from Europe, the Middle East and Western India.